Multi-class bandwidth reservation scheme based on mobility prediction for handoff in multimedia wireless/mobile cellular networks. - Sanabani, Maher Ali; Subramaniam, Shamala; Othman, Mohamed; Ahmad Zulkarnain, Zuriati (Springer Verlag, 2008)
Next generation of wireless cellular networks aim at supporting a diverse range of multimedia services to Mobile Terminal (MT) with guaranteed Quality of Service (QoS). The challenge is to maintain the playing continuity of multimedia streams during handoff. In this paper, a bandwidth reservation scheme based on mobility prediction is proposed, to enable high accurate prediction of next crossing cell (target cell) which a MT is going to, in order to avoid too early or over reservation resulting in a waste of resources. The amount of bandwidth to be reserved is dynamically adjusted according to (a) the current position (location) and the extrapolated direction of MT and; (b) the sector and zones of the cell. A Call Admission Control scheme (CAC) is also considered to further guarantee the QoS of real time traffic. The performance of the system is evaluated through discrete event simulation of the wireless cellular environment. Simulation results show that the proposed scheme as compared to several existing schemes is able to reduce the Handoff Call Dropping Probability (HCDP) of real time traffic and the number of terminated ongoing calls of non-real time traffic. In addition, it is efficient to reduce the number of cancelled reservation and subsequently increase the system bandwidth utilization.